André Tavares, Architecture Follows Fish: An Amphibious History of the North Atlantic, 2024 - Motta, Martina (Studi e ricerche di storia dell’architettura, 2026)
Recensione del volume André Tavares, Architecture Follows Fish: An Amphibious History of the North Atlantic (The MIT Press, 2024).